TUTURAN ILOKUSI DALAM NOVEL BULAN TERBELAH DI LANGIT AMERIKA KARYA HANUM SALSABIELA RAIS DAN RANGGA ALMAHENDRA - Eka Setia Pratiwi; Hasnah Faizah; Hermandra ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research discusses Speech in Bulan Terbelah di Langit Amerika by Hanum Salsabiela Rais and Rangga Almahendra.This study aimed to find forms of speech illocutionary contained in the novel Moon Cleft in the Sky America Salsabiela Rais Hanum work and Rangga Almahendra. The research is a qualitative research with descriptive methods. This research data is the meaningful speech illocutionary assertive, directive, expressive, commissive, and declarative. Data obtained using the technique of reading and validity of the data obtained by the technique trianguasi. Then, the data were analyzed by identifying and classifying based illocutionary speech. Based on data analysis has been done, the authors found a significant assertive form illocutionary speech suggested, expressed, inform and complain. Illocutionary speech directive forms with meaning reigns, beg, recommend, encourage and advise. Illocutionary speech expressive form meaningful thank, praise, apology and condolences. Illocutionary speech commissive meaningful form swearing and offers and illocutionary speech declarative form meaningful resignation.Keywords: Speech Act, Illocutionary Speech, and Novel